ANALISIS KANDUNGAN ZAT-ZAT MAKANAN KULIT BUAH KAKAO YANG DIFERMENTASI DENGAN Trichoderma sp. SEBAGAI PAKAN TERNAK RUMINANSIA - Syahrir, Syahrir (FAPETKAN UNTAD, 2005)
The study was aimed at investigating the interacting effects of Â Trichoderma sp. dosage and fermentation period on nutrient contents of cocoa pod. The work was carried out in Animal Feed and Nutrition Laboratory, Department of Animal Husbandry, University of Â Tadulako. The first factor was Trichoderma sp dosage (2 levels) while the second factor was period of fermentation (3 levels). Analysis of variance showed that there was no interacting effect between the two factors on all parameters observed, but there were significant effects of each of individual main factor. Period of fermentation affected dry matter, crude fibre and protein contents highly significantly (P<0.01) and ash and crude lipid contents signficantly (P<0.05). Dosage of Trichoderma sp. used in fermentation showed a highly significant effect (P<0.01) on dry matter content only. Key words : Cocoa pod, nutrient content, fermentation , ruminants.